Behçet's disease departs the 'Silk Road': a case report and brief review of literature with geographical comparison. Issue 1 (1st January 2016) - Ahmed, Zohair; Rossi, Maria L.; Yong, Sherri; Martin, Daniel K.; Walayat, Saqib; Cashman, Michael; Tsoraides, Steven; Dhillon, Sonu
Abstract : Behçet's disease (BD) is a chronic multisystem inflammatory disease most prevalent in Eastern Asia and along the Mediterranean basin, an area referred to as the 'Silk Road'. The diagnosis of BD is largely based on the International Study Group (ISG) criteria, which are more specific than sensitive. ISG criteria do not include intestinal manifestations, a feature more commonly seen in the West. Intestinal BD is one of several findings that are not typically seen along the 'Silk Road'. Herein we report a rare case of intestinal BD and compare Western versus traditional BD. A 25-year-old male with a history of painful oral aphthous ulcers, pericarditis, and diffuse papulopustular rash presented to the emergency department with two terminal ileal perforations. Pathology demonstrated mucosal necrosis with active inflammation and no chronic inflammatory changes. Post-surgical laboratory studies showed an elevated c-reactive protein of 35.57 mg/dL, erythrocyte sedimentation rate of 82 mm/h, and a positive anti- Saccharomyces cerevisiae antibody. Rheumatological workup including ANA, RF, PR3 antibody, MPO antibody, ANCA, SSA and SSB, Smith antibody, SCL-70, and anti-Jo-1 antibodies were all negative. His pericarditis symptoms improved with colchicine and prednisone prior to discharge. Our patient did not meet the current ISG criteria for traditional BD; however, he clearly showed findings typically seen in Western patients with BD, which include intestinal manifestations, cardiac involvement, and lack of pathergy reaction and ocular changes. Our investigation demonstrates that the clinical manifestations common to this disorder vary among geographic and ethnic populations. Commonly used criteria for the diagnosis of BD may not be sensitive for some populations, such as Western BD, potentially leading to underdiagnoses and mismanagement. Recognition and select inclusion of these differences may be one way to assist with diagnosing Western BD in the future. As our knowledge of BD continues to evolve, so must the population-specific criteria used to define BD.